Levy processes and their applications in reliability and storage - Abdel-Hameed, Mohamed (SpringerBriefs in Statistics, 2014)
This book covers Lévy processes and their applications in the contexts of reliability and storage. Special attention is paid to life distributions and the maintenance of devices subject to degradation; estimating the parameters of the degradation process is also discussed, as is the maintenance of dams subject to Lévy input.